Efektifitas Terapi Musik Klasik Mozart dan Terapi Murotal Surah Ar-Rahman terhadap Penurunan Tingkat Stres Akademik Remaja - Anisaul Chusnia; Sunarko Sunarko; Bambang Sarwono; Sunarmi Sunarmi (JURNAL KEPERAWATAN MERSI, 2018)
Background:  Stress is a condition of physical and psychological stress due to demands in self and the environment. Monotonous situations, too many tasks, frivolous hopes, danger conditions and critical, unappreciated, ignored . This study aims to determine the effectiveness of Mozart's classical music therapy and Ar-Rahman's murotal therapy on reducing adolescent academic stress levels .  Method: The sample technique of this study was total sampling of 31 people. The type of research was pre-experimentation in the pre-test and post-test group design . Statistical data analysis meng use  WilcoxonTest . Data collection was carried out before and after being given classical music therapy using SLSI Instruments . Results:  Wilcoxon test result stress levels before and after the second classical music therapy results obtained significance value of 0.000 which is smaller than α = 0,05. Decrease in the number of respondents prior to the classical music therapy at stress levels of academic was 4 children (11.4%) and kat egori low is 8 children (22.8%). After therapy music   classic Mozart category higher that 2 children (5.7%) and the category of low, namely 3 children (8.6%). The level of stress academic before do therapy murottal Surah Ar-Rahman category of high- ie 4 children (11.4%) categories of lower her 4 children (11.4%), after treatment murottal Surah Ar-Rahman category of high 2 children (5.7%) and the category of low 3 children (8.5%). The results of diff mann whitney test obtained p value 0,000 with mean rank classical music therapy 44.93 and 26.07 for murotal therapy . Conclusion: Based on the study of classical music therapy is more effective in lowering the level of stress academic.